Late-onset major depression is associated with age-related white matter lesions in the brainstem - Schwichtenberg, Johannes; Al-Zghloul, Mansour; Kerl, Hans Ulrich; Wenz, Holger; Frölich, Lutz; Groden, Christoph; Förster, Alex (International journal of geriatric psychiatry, 2017)
Objective Age-related white matter lesions (ARWMLs) have been identified in various clinical conditions such as reduced gait speed, cognitive impairment, urogenital dysfunction, and mood disturbances. Previous studies indicated an association between ARWML and late-onset major depression. However, most of these focused on the extent of supratentorial ARWML and neglected presence and degree of infratentorial lesions. Methods In 45 patients (mean age 73.7 ± 6.3 years, 17 (37.8%) men, 28 (62.2%) women) with late-onset major depression, MRI findings (3.0-T MR system, Magnetom Trio, Siemens Medical Systems, Erlangen, Germany) were analyzed with emphasis on the extent of supratentorial and infratentorial, as well as brainstem ARWMLs, and compared with control subjects. ARWMLs were determined by semiquantitative rating scales (modified Fazekas rating scale, Scheltens' rating scale), as well as a semiautomatic volumetric assessment, using a specific software (MRIcron). Supratentorial and infratentorial, as well as brainstem ARWMLs, were assessed both on fluid attenuated inversion recovery and T2-weighted images. Results Patients with late-onset major depression had significantly higher infratentorial ARWML rating scores (5 (5-7) vs 4.5 (3-6), p = 0.003) on T2-weighted images and volumes (1.58 ± 1.35 mL vs 1.05 ± 0.81 mL, p = 0.03) on T2-weighted images, as well as fluid attenuated inversion recovery images (2.07 ± 1.35 mL vs 1.52 ± 1.10 mL, p = 0.04), than normal controls. In more detail, in particular, the pontine ARWML rating subscore was significantly higher in patients with late-onset major depression (1 (1-2) vs 1 (1-1), p = 0.004). Conclusions The extent and localization of brainstem ARWML might be of importance for the pathophysiology of late-onset major depression. In particular, this may hold true for pontine ARWML.